2017
DOI: 10.1111/jasp.12469
|View full text |Cite
|
Sign up to set email alerts
|

So close and yet so far away: A psychological distance account of the effectiveness of leader appeals

Abstract: Contradictory recommendations persist on how leaders best communicate goals to followers. Whereas scholars of visionary leadership recommend emphasizing the desirability of preferred end‐states, scholars of goal setting argue that the perceived feasibility of a goal determines motivation. This paper proposes and tests a synthesis based on construal level theory. Under relatively high (i.e., abstract) levels of construal, such as when leader–follower distance is relatively large, leader appeals that emphasize d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 97 publications
(165 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, it is important to recognize that the effect of visioning may be contingent on the psychological distance that exists between followers and leaders (Berson et al, 2015). Recall that van Houwelingen and colleagues (2017) recently demonstrated that desirability appeals, which are seen as characteristic of visions (van Knippenberg & Stam, 2014), were more effective when leader-follower spatial distance was high. This speaks to the importance of integrating antecedents and consequences of visionary leadership in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is important to recognize that the effect of visioning may be contingent on the psychological distance that exists between followers and leaders (Berson et al, 2015). Recall that van Houwelingen and colleagues (2017) recently demonstrated that desirability appeals, which are seen as characteristic of visions (van Knippenberg & Stam, 2014), were more effective when leader-follower spatial distance was high. This speaks to the importance of integrating antecedents and consequences of visionary leadership in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of empirical research, van Houwelingen, van Dijke, and De Cremer (2015) showed that construal level influences leaders’ decision to discipline followers after transgression of moral norms. Demonstrating the importance of a match between the situation and leader communication in terms of construal level, van Houwelingen, Stam, and Giessner (2017) found that leader appeals to desirability (feasibility) were more effective when the spatial distance between leaders and followers was high (low). These developments suggest that construal level holds promise for explaining leadership phenomena, and we suspect that leader vision communication is a promising candidate given the parallels between visions and high-level construal in terms of temporal perspective and abstraction.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, leadership scholars have noted a myriad of issues with the transformational leadership construct and have advocated for research to “examine more empirically distinct aspects of leadership” (Van Knippenberg & Sitkin, 2013, p. 2). Indeed, many researchers have begun to examine leader vision communication in isolation, and vision communication is a growing construct in leadership research (e.g., Carton & Lucas, 2018; Kearney, Shemla, van Knippenberg, & Scholz, 2019; van Houwelingen, Stam, & Giessner, 2017).…”
Section: Gender Diversity and The Cemmentioning
confidence: 99%
“…Moreover, as psychological distance decreases, the object or event is more likely to be represented in terms of concrete, detailed, and contextualized features, often referred to as low‐level construals (Liberman et al., 2002; Liberman & Trope, 1998; Trope & Liberman, 2003). More importantly, such varying mental construals are found to affect individuals preference, attitude, and behavior differently (van Houwelingen et al., 2017; Liberman et al., 2007; Trope & Liberman, 2010; Trope et al., 2007; Zhuang et al., 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The former is linked to subordinate means (i.e., feasibility: the "how" of the action), whereas the letter is associated with superordinate purpose (i.e., desirability: the "why" of the action). Many communication scholars have applied this desirability-feasibility distinction to message designs and found that these appeals affect consumes at different levels of mental construal, and in turn, guide their attitudes and behaviors (Liberman et al, 2007;Trope & Liberman, 2010;Trope et al, 2007).…”
mentioning
confidence: 99%